DEVELOPMENT OF MANIPULATIVE BASIC MOTION LEARNING MODEL AT MENTALLY RETARDED ELEMENTARY SCHOOL IN MEDAN CITY - DEWI, RATNA (ACPES 2017, 2017)
Adaptive physical education is a vehicle that provides Children with Special Needs learning aboutvarious theoretical and practical theoretical material. Adaptive physical education also presents avariety of sports activities tailored to the characteristics of children with special needs, including blind,deaf, learning disabilities, orthopedically handicapped, and conduct disorder. Characteristics ofchildren with special needs are based on formal education or special schoolsare classified into severalcategories. While other types, still have the opportunity to be able to formal education in regularschools.Also, with the phenomenon contained in the city of Medan, which have the number of learningdisabilities more than any other type of School For Student with Special Needs category. Based onobservation result, sport activity for children with special needs in, especially in category learningdisabilities in Medan is still less varied. Sports activities, especially basic motion that is less varied,will certainly result in the students (children with special needs) feel bored. If you feelbored,thedirection and purpose of learning more difficult to achieve. Therefore, to accommodate learning,especially in the realm of adaptive physical education, it is necessary to undertake various forms ofdevelopment of existing sports activities specifically, especially at an early age. It is aimed to mastersustained basic motion based on certain age stages, either in curative or in terms of achieving the bestachievement in various special needs childrens championship at district and provincial level.The method used in this research is the type of research & development. Research & development (R& D) aims to create a product that is intended to overcome a problem in the field. The products that tryoffered by researchers in the form of manipulative basic motion game package intended for studentsoflearning disabilities at elementary level (elementary school). The product will be packaged in theimplementation guide as well as the VCD game implementation tutorial. This game package isconsidered capable of being a good introduction before students (Student with special need) leads tomore complicated material. Where students will get the sensation of playing while learning toimplement basic manipulative motion, before students do the sports. In the first year, researcherscompiled a basic manipulative motion game for elementary school students, and the second year, theresearchers measured the level of influence of the manipulative base motion to the learning outcomesof the learning disabilities students